Acute cellular rejection the first year after heart transplantation and its impact on survival: a single‐centre retrospective study at Skåne University Hospital in Lund 1988–2010. (26th March 2014) - Söderlund, Carl; Öhman, Jenny; Nilsson, Johan; Higgins, Thomas; Kornhall, Björn; Johansson, Leif; Rådegran, Göran
Summary Acute cellular rejection (ACR) the first year after heart transplantation (HT) and its impact on survival was investigated. All 215 HT patients at our centre 1988–2010, including 219 HTs and 2990 first‐year endomyocardial biopsies (EMBs), were studied. 'Routine' EMBs obtained 1, 2, 3, 4, 6, 8, 10, 12, 16, 20, 24, 32, 40 and 52 weeks after HT, and 'additional clinically indicated' (ACI) EMBs, were graded according to the 1990‐ISHLT‐WF. The frequency and severity of first‐year ACRs was low, with 6.5% of routine EMBs and 14.1% of ACI EMBs showing ACR ≥ grade 2. Proportionally more (P < 0.05) first‐year ACRs ≥ grade 2 were found among EMBs in HTs performed during 1988–1999 (9.6%) than 2000–2010 (5.5%), EMBs performed during 16–52 weeks (8.8%) than 1–12 weeks (6.3%) after HT, EMBs in HTs with paediatric (11.3%) than adult (7.1%) donors, and EMBs in sex‐mismatched (10.4%) than sex‐matched (6.3%) HTs. Five‐ and ten‐year survival was furthermore lower (P < 0.05) among HTs with ≥1 compared with 0 first‐year ACRs ≥ grade 3A/3B (82% vs. 92% and 69% vs. 82%, respectively). Ten‐year survival was 74% compared with 53% in the ISHLT registry. In conclusion, our results indicate that first‐year ACRs ≥ grade 3A/3B affect long‐term survival. We believe frequent first‐year EMBs may allow early ACR detection and continuous immunosuppressive adjustments, preventing low‐grade ACRs from progressing to ACRs ≥ grade 3A/3B, thereby improving survival.